EXTRACTION AND RECOVERING OF FINGER VEIN VERIFICATION BASED ON DEEP ATTRIBUTE REPRESENTATION - Kumar, B. Muthu; Ragaventhiran, J.; Bhavana, N.; Pandian, M. Thurai; Islabudeen, M.; Sampath, A. K. (Malaysian Journal of Computer Science, 2022)
A finger vein authentication system is proposed in this research. Biometrics is the science of determining a person’s identity based on physiological or behavioral characteristics. Physical characteristics like fingerprints, a face or a retina, as well as personal characteristics like a signature, are included in these characteristics. Biometric features are significantly more difficult for attackers to replicate or fabricate than traditional methods, and they are extremely rare to lose. Biometric traits are used in the identification system, which increases security and dependability. The technology to verify vein patterns is still relatively new, compared with other human characteristics. The proposed work focuses on developing a contactless sensor to retrieve features from the hand’s finger vein pattern using a Deep attribute Representation based Fractional Firefly method (DAR-FFF). Vein pattern identification scans the blood for hemoglobin using an infrared light source. After the participant’s palm is placed over the sensing device, an infrared region beam from the device measures the orientation of the arteries. These ultraviolet wavelengths are absorbed by liquid hemoglobin in the vasculature, resulting in dark streaks on the map. The hand’s finger has more intricate circulatory pathways and a variety of distinguishing characteristics. Image enhancement, skeletonization, and vein pattern chain code comparison are all processes in this procedure.